Factorise: 4(2a + B)2 - (A - B)2 - Mathematics

Advertisement Remove all ads
Sum

Factorise: 4(2a + b)2 - (a - b)2  

Advertisement Remove all ads

Solution

4(2a + b)2 - (a - b)2  

= [2(2a + b)]2 - (a - b)2 

= [2(2a + b) + a - b][2 (2a + b) -a + b]

= (4a + 2b + a - b)(4a + 2b - a + b)

= (5a + b)(3a + 3b)

= (5a + b) 3(a + b)

= 3 (5a + b) (a + b)

Concept: Factorisation by Difference of Two Squares
  Is there an error in this question or solution?

APPEARS IN

Selina Concise Mathematics Class 8 ICSE
Chapter 13 Factorisation
Exercise 13 (C) | Q 10 | Page 159
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×